Investigation of the potential applications of shape memory alloys for space debris remediation applications - Feng, Louis Wei-Yu (Department of Electrical Engineering, 2019)
Active debris removal is becoming an important area of research due to the rapid growth of space debris and the need for some form of debris remediation. Debris remediation concepts fall into two general categories: contactbased and contactless. Contact-based schemes for debris capture have to overcome the challenge of capturing a noncooperating object in space with no pre-designed attachment points. Various schemes involving, inter alia, nets and harpoons have been proposed. In this paper we explore the potential to use shape-memory alloys as a technological basis for a debris capturing solution that can be used multiple times. A proof-of-concept prototype was developed at the University of Cape Town, named MEDUSA (Mechanism for Entrapment of Debris Using Shape memory Alloy). This has been designed as a validation payload for a CubeSat test platform to perform a small debris capture proofof-concept demonstration. MEDUSA uses the shape-memory alloy ninitol, which gives it the ability to assume preprogrammed “open” and “closed” shapes after distortion. Each of the five arms of MEDUSA can attain both preprogrammed shapes to allow reversible operations. This paper presents the design and development process from the conceptual design to the current Mk-III prototype, this work is an improvement based on the prototype Mk-II. The device has completed thermal and vacuum testing at the Institute for Space Systems in Stuttgart Germany to assess its performance under various environmental conditions.